PTPIP51 levels in glioblastoma cells depend on inhibition of the EGF-receptor - Petri, Meike Katinka; Brobeil, Alexander; Planz, J.; Bräuminger, A.; Gattenlöhner, Stefan; Nestler, U.; Stenzinger, Albrecht; Paradowska-Dogan, Agnieszka; Wimmer, M. (Journal of neuro-oncology, 2015)
Protein tyrosine phosphatase interacting protein 51 (PTPIP51) is upregulated in glioblastoma multiforme (GBM) and expression levels correlate with the grade of malignancy in gliomas. A similar correlation was reported for its interacting partner 14-3-3β, which has been shown to facilitate the interaction of PTPIP51 with cRAF (Raf1). Since the interaction of these signalling partners stimulates growth factor signalling downstream of the epidermal growth factor receptor (EGFR), a major drug target in GBM, we here investigated the impact of EGFR inhibition by small molecule inhibitors or monoclonal antibody on PTPIP51. The effect of EGFR inhibition on PTPIP51 mRNA, protein expression and its interaction profile in GBM was analyzed using the U87 cell line as model system. The transferability of the results to in vivo conditions was evaluated in cultured tumour cells from GBM patients. Cells were treated either to the small molecule tyrosine kinase inhibitor of EGFR Gefitinib or the monoclonal antibody Cetuximab in a time and dose dependent manner. Gefitinib treatment decreased the proliferation rate and induced apoptosis in U87 and primary tumour cells. The PTPIP51 interaction profile changed in correlation to the applied Gefitinib. Despite unchanged mRNA levels PTPIP51 protein was reduced. In contrast, treatment with Cetuximab had no effects on PTPIP51 expression. In conclusion, our results demonstrate the impact of EGFR inhibition by Gefitinib on PTPIP51 protein expression, a downstream regulator of MAPK signalling. These data will serve as a basis to unravel the precise role of PTPIP51-mediated signalling in GBM and its potential implications for Gefitinib-mediated therapy in future studies.